Disturbed acid-base transport: an emerging cause of hypertension - Boedtkjer, Ebbe; Aalkjaer, Christian (Frontiers in Physiology, 2013)
Genome-wide association studies and physiological investigations have linked alterations in acid-base transporters to hypertension. Accordingly, Na+-coupled HCO3–transporters, Na+/H+-exchangers, and anion-exchangers have emerged as putative mechanistic components in blood pressure disturbances. Even though hypertension has been studied extensively over the last several decades, the cause of the high blood pressure has in most cases not been identified. Renal, cardiovascular, and neuronal dysfunctions all seem to play a role in hypertension development but their relative importance and mutual interdependency are still being debated. Multiple functional and structural alterations have been described in patients and animals with hypertension but it is typically unclear whether they are causes or consequences of hypertension or represent mechanistically unrelated associations. Perturbed blood pressure regulation has been demonstrated in several animal models with disrupted expression of acid-base transporters; and reciprocally, disturbed acid-base transport function has been described in hypertensive individuals. In addition to regulating intracellular and extracellular pH, Na+-coupled HCO3–transport, Na+/H+-exchange, and anion-exchange also contribute to water and electrolyte balance in cells and systemically. Since acid-base transporters are widely expressed, alterations in transport activities likely affect multiple cell and organ functions, and it is a significant challenge to determine the mechanisms linking perturbed acid-base transport function to hypertension. It is the purpose of this review to evaluate the current evidence for involvement of acid-base transporters in hypertension development and discuss the cellular and integrative mechanisms, which may link changes in acid-base transport to blood pressure disturbances.